2021
DOI: 10.3389/fvets.2020.619030
|View full text |Cite
|
Sign up to set email alerts
|

Animal Production With Restrictive Use of Antibiotics to Contain Antimicrobial Resistance in Sweden—A Qualitative Study

Abstract: Antibacterial resistance (ABR), is a growing global threat to human and animal health. Efforts to contain ABR are urgently needed. This qualitative interview study explored perceptions of work to contain ABR among stakeholders in food animal production in Sweden, with focus on broiler production. Semi-structured interviews were carried out with a strategic sample of 13 stakeholders in different parts of production, from professionals at policy level, veterinary authorities, to poultry farmers and poultry veter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…The situation in Swedish broiler production is very good since the use of antibiotics is infrequent [ 34 ]. Consequently, the prevalence of resistant bacteria isolated from animals in Sweden is low [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The situation in Swedish broiler production is very good since the use of antibiotics is infrequent [ 34 ]. Consequently, the prevalence of resistant bacteria isolated from animals in Sweden is low [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Encouraging rational AMU is a fundamental principle of antimicrobial stewardship programs (ASPs). In veterinary practice, a range of approaches have been adopted across Europe including the imposition of regulations restricting the use of specific antimicrobials and the promotion of voluntary antimicrobial stewardship guidelines (ASGs) at the national and clinical levels [14][15][16][17][18][19][20][21]. Restrictive policies limiting the use of particular antimicrobials in food-producing animals are already in place in several European countries and will come into force across the European Union in January 2022 [22].…”
Section: Introductionmentioning
confidence: 99%
“…Evaluating the effect of the policies is not the scope of this paper, but data show that Sweden has low and decreasing consumption of antibiotics for both human and veterinary use in an international comparison [18][19][20]26]. Qualitative studies conducted as part of the ABR CARRO project by our research team have shown that actors both in the human, veterinary, and environmental sectors perceive the Swedish work on AMR to be well known and established among most stakeholders in the various sectors [35][36][37]. Most stakeholders feel that a lot has been achieved in Sweden regarding antibiotic resistance containment but that there is still room for increasing awareness and emphasising changes in behaviour and attitudes among prescribers and the public.…”
Section: Discussionmentioning
confidence: 99%
“…Most stakeholders feel that a lot has been achieved in Sweden regarding antibiotic resistance containment but that there is still room for increasing awareness and emphasising changes in behaviour and attitudes among prescribers and the public. With regards to the term "One Health" itself, knowledge among stakeholders was relatively low [35][36][37].…”
Section: Discussionmentioning
confidence: 99%